Western Australian Late Cretaceous and Cenozoic brachiopoda. - Craig, Robert S. (Curtin University, 1999)
The research reported in this thesis focuses on Late Cretaceous and Cenozoic fossil brachiopods of Western Australia. Although the work is primarily taxonomic, it also includes biodiversity, distribution and some aspects of ecology of the brachiopods described.The most recent information on the anatomy, physiology and ecology of brachiopods is summarised at the beginning of the thesis.Identification of brachiopods is determined primarily on internal morphological features as brachiopods tend to be homomorphic, many species looking externally the same. The morphological features used in the identification of the brachiopods described within the thesis are defined.The fossil material studied has come from four sedimentary basins in Western Australia. The Carnarvon Basin contains Late Cretaceous and Cenozoic fossil material. The Perth Basin also has Late Cretaceous and late Cenozoic brachiopods The Bremer and Eucla Basin have Cenozoic deposits. The stratigraphy of the deposits containing the brachiopods is described.Until this study commenced, eight species had been described from Western Australia. This thesis describes fifty eight species including thirty new species, one new family and two new genera.In preparing descriptions of the new species it become evident that many of the species from the Southern Hemisphere were quite different to those found in the Northern Hemisphere. Their closest affiliation was with genera and species described from the Antarctic Peninsula. Four genera and one species from the Late Cretaceous deposits of Western Australia are common to the Late Cretaceous deposits of the Antarctic Peninsula. In the examination of the Tertiary material from the Carnarvon Basin, it also became clear that there was a strong correlation with Tertiary material from the Antarctic Peninsula. At least four genera are common to both deposits. Six brachiopod genera from the Middle Miocene deposits of the South Shetland Islands Antarctica are common to New Zealand. Nine genera, identified from the La Meseta Formation, Seymour Island, Antarctic Peninsula, are also common to New Zealand. These genera are also found in Australia. This evidence has led to the proposal that in the Late Cretaceous there was a common shelf environment from the Antarctic Peninsula to the north-west coast of Western Australia. In this area, which formed the high latitude southern circum-Indo-Atlantic faunal province, brachiopods evolved different genera and species than those in the northern hemisphere. Many then dispersed into northern areas of the Indian, Atlantic and finally Pacific Oceans.When the material from the Middle to Late Eocene of the Bremer and Eucla Basin was examined, five genera were found to be common to the Early Tertiary of the Carnarvon Basin. When comparing the species from the south-western basins and those from the south- east it was evident that similar species occur in the Middle to Late Eocene of the Bremer, Eucla, St Vincent and Murray Basins. There are some fifteen species in common. Many of these species then occur in the Late Oligocene south-eastern basins near Victoria and Tasmania as the gap between the Australia mainland and Tasmania began to open. One species that occurs in the Late Eocene of Western Australia is also described from the Late Oligocene of New Zealand.In considering the distribution of the Cenozoic brachiopods, genera first appear in the north-west of Western Australia and they then appear in chronological order in the south-western basins and south-eastern basins of South Australia, then the south-eastern basins of Victoria and Tasmania and then New Zealand. By the Late Eocene, there was a shallow marine connection between the Bight and the Tasman Sea. By the Late Oligocene this had widened and Australia was finally totally separated from Antarctica.The Proto-Leeuwin Current was responsible for the distribution of the brachiopods from the north-west of Western Australia to the southern coast. Possible mechanisms for the distribution of genera to New Zealand include rafting and an extended larval stage.It has been suggested that brachiopods in Australia are distributed according to the substrate on which they settle rather than any other factor. Using the information on the distribution of brachiopods in Western Australia throughout the Cenozoic this hypothesis is examined. It is suggested that avoidance of light in the photic zone and food availability with competition with bivalves are more important factors than substrate conditions.